The Psychosocial Wellbeing of Children with Disabilities in Inclusive Secondary School Education Settings - Mbatt, Ignasia Paskal; Philip, Eugen Mtemi (Educational Challenges, 2024)
Purpose. This study examined the psychosocial wellbeing of children with disabilities in inclusive secondary school education setting in Tanzania. The study particularly aimed to explore the psychosocial challenges which children with disabilities face in inclusive secondary school settings, leading to psycho-social impacts on their learning and wellbeing. Methodology. The study employed a mixed methods approach, adopting a case study design. Interviews and questionnaires were used to collect data from 49 students with special needs, 7 special needs education teachers, and 35 regular teachers. Results. The study findings revealed that teachers had low expectations on the academic performance of the students with disabilities, consequently rendering them little support in inclusive classrooms. Additionally, discrimination, stigmatisation were issues faced by students with disabilities in inclusive education settings which adversely affected their psychosocial wellbeing. The study recommends awareness creation among the students and regular teachers about the learning needs of children with disabilities in inclusive schools. Conclusions. The study recommends providing regular teachers who are not knowledgeable about the academic needs of students with disabilities in inclusive education settings with training and providing psychosocial support to students with special needs in inclusive education contexts.